Paussus (Edaphopaussus) asseyi sp. nov. (Coleoptera: Carabidae: Paussinae) from the Nguru Mountains of the Eastern African Arc in Tanzania - Bednařík, Michal; Bocak, Ladislav (Zootaxa, 2023)
A new species of Paussus L., 1775 (Coleoptera: Carabidae) is described from the Nguru Mountains of the Eastern African Arc in Tanzania. Paussus asseyi sp. nov. is diagnosed by the shape of the antennal club, which bears two sharp edges at the outer margin, the blunt spines on tibiae, and the characteristic colouration that allows this species to be distinguished from all other species in Paussus (Series I) defined in the latest molecular phylogeny. Other characters, i.e., the shape of the pronotum and absent pronotal setae, place the new species in the subgenus Edaphopaussus Kolbe, 1920. The colouration resembles P. dichrous Janssens, 1950 from Democratic Republic Congo and Angola and some Asian species, yet all are morphologically different from the new species. The robust head, small eyes, and clypeus shape resemble distantly related P. (Hylotorus) cephalotes Raffray, 1886. The individual mountain massifs of Eastern Tanzania represent rainforest islands set in much drier lowlands with savannah ecosystems. The new species contributes to our understanding of the isolated mountain ranges’ relatively poorly investigated beetle fauna.